Cognitive coaching: stengthening the capacity of Grade R teachers to enhance the teaching practice of student teachers - Rutgers, Linda; Reddy, Chris (South African Journal of Higher Education, 2016)
Effective lesson planning and analysis are important aspects of teaching and any innovative partnership between universities and schools to improve teaching practice in the Early Childhood Development sector is a sound investment in the future of our young learners. In this paper I report on a collaborative partnership that was initiated between the University of Stellenbosch and Grade R teachers. The purpose of this initiative was to provide support and share expertise amongst the various role players in the partnership and to enhance classroom teaching practice and lesson planning in the ECD sector through cognitive coaching. The research project explored the contribution of cognitive coaching on the leadership practice of Grade R teacher participants and the teaching practice of the student teachers in the Grade R classroom. Results from the research indicate that the partnership has had positive effects for all the stakeholders in the process and that real benefits accrue with time as expertise and competence improves confidence in the work contexts of ECD teachers and practitioners.